Ameliorative Effect of Wood Biochar for Cadmium Stress on Soybean (Glycine Max L. Merrill) Growth and Yield - Muhammad Abdus, Sobahan (SAARC Journal of Agriculture, 2023)
Cadmium (Cd) is a heavy metal that affects plant growth and yield. Biochar can mitigate the detrimental effect of Cd on plants. To assess effectiveness of wood biochar (WB) in mitigating Cd stress, a pot experiment was conducted with six treatments in Soyabean crop viz., control (0% biochar and no Cd stress), 1.5% WB, 3% WB, 100 mg CdCl2 Kg-1 soil, 100 mg CdCl2 Kg-1 soil +1.5% WB, 100 mg CdCl2 Kg-1 soil +3% WB. The impact of Cd on the growth, physiological status, yield and yield-contributing characters of Soybean were found to be significant (p<0.05). The application of 1.5% and 3% WB significantly (p < 0.05) alleviated Cd toxicity to Soybean under Cd stress conditions. There was no significant difference in the effect of two rates of wood biochar’s (1.5% and 3% WB) on growth, physiological status and yield of Soybean. Therefore, it can be concluded that 1.5% WB is sufficient to reduce toxicity caused by Cd stress in Soybean. SAARC J. Agric., 21(2): 157-168 (2023)